Non-US global banks and dollar (co-)dependence: how housing markets became internationally synchronized - Torsten Ehlers; Mathias Hoffmann; Alexander Raabe (Graduate Institute of International and Development Studies, 2020)
US net capital inows drive the international synchronization of house price growth. An increase (decrease) in US net capital inows improves (tightens) US dollar funding conditions for non-US global banks, leading them to increase (decrease) foreign lending to third-party borrowing countries. This induces a synchronization of lending across borrowing countries, which translates into an international synchronization of mortgage credit growth and, ultimately, house price growth. Importantly, this synchronization is driven by non-US global banks' common but heterogenous exposure to US dollar funding conditions, not by the common exposure of borrowing countries to non-US global banks. Our results identify a novel channel of international transmission of US dollar funding conditions: As these conditions vary over time, borrowing country pairs whose non-US global creditor banks are more dependent on US dollar funding exhibit higher house price synchronization.
Keywords: F34; F36; G15; G21; 330; house price synchronization; US dollar funding; global US dollar cycle; global imbalances; capital inows; global banks; global banking network